Grotesque Encounters: An Archetypal Analysis of Psychic Symbolism in Fairy Tales - Khan, Imdad Ullah; Shah, Syed Dawood; Yaseen, Raheela Naz (Pakistan Languages and Humanities Review, 2025)
This study examines the fairy tales Bluebeard and Beauty and the Beast through the lens of Jungian analytical psychology, specifically focusing on archetypal motifs that symbolize the individuation process. It delimits its scope to psychic transformation, the grotesque, and feminine agency. While traditional analyses emphasize moral or sociocultural themes, this research explores how fairy tales dramatize the integration of unconscious elements into conscious awareness. The study addresses a scholarly gap by emphasizing archetypal structures and inner psychic development in these narratives. Employing a qualitative method and Jungian theoretical framework, the tales are analyzed for archetypal imagery such as the shadow, anima/animus, and the process of individuation. Central symbols and narrative moments are deconstructed to reveal deeper psychological meaning. In Bluebeard, the key and forbidden chamber represent repressed aspects of the psyche and the cost of denial of psychic elements. In Beauty and the Beast, the Beast embodies the shadow, with transformation enabled through empathy. Both tales depict inner confrontation and conscious awareness as essential to personal growth. In light of the current study, it is recommended that literary and psychological interpretations of fairy tales incorporate archetypal analysis to deepen understanding of the unconscious. Educators and therapists might also use these tales to support personal insight and emotional integration.